2018
DOI: 10.9770/jssi.2018.7.4(5)
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of Institutional Responsibility in Climate Change Risk in Baltic Nordic Countries

Abstract: Tackling climate change requires collective, cross-borders actions and local solutions for mitigation measures. Variety of actors are involved in climate change adaptation and mitigation, ranging from local communities to the global supranational institutions. People tend to perceive individual action as failing to cope with climate change (e.g. outlined in Lorenzoni and Pidgeon, 2006) and therefore ascribe high responsibility to the institutional level. This article will analyze how the public in Baltic -Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Baltic States climate change topic is prescribed as political issue, with no personal responsibility in it. Balžekienė et al (2008) and Budžytė and Balžekienė (2018) support the same findings. Opposite situation appears in Slavic countries, lack of political and governmental initiative solving climate change problems is a huge challenge in these countries.…”
Section: Contextual Parameters Of Infromationmentioning
confidence: 53%
See 1 more Smart Citation
“…Baltic States climate change topic is prescribed as political issue, with no personal responsibility in it. Balžekienė et al (2008) and Budžytė and Balžekienė (2018) support the same findings. Opposite situation appears in Slavic countries, lack of political and governmental initiative solving climate change problems is a huge challenge in these countries.…”
Section: Contextual Parameters Of Infromationmentioning
confidence: 53%
“…In Baltic Sea Region (BSR) climate change awareness increasing. However the levels of information perception are different in Baltic -Nordic countries (Budžytė and Balžekienė, 2018). Kažys (2016) found that the climate change information content in the internet holds higher quality in Western BSR countries than in Eastern ones.…”
Section: Introductionmentioning
confidence: 99%
“…Cli mate change ranks first (51% of respondents mentioned it), followed by air pol lution (46%) and the growing amount of waste (40%). 2 These results vary by country, as well. The Nordic states of the Baltic region are most concerned about climate change (70% in Denmark, 68% in Sweden, 63% in Germany and Fin land); Poles are worried about air pollution; the growing amount of waste is the number one issue in Lithuania (65%), Latvia (61%), and Estonia (54%).…”
Section: Studies Of Environmental Risk Perception In Baltic Region Statesmentioning
confidence: 94%
“…1 Attitudes of European citizens towards the environment, Special Eurobarometer 468, available at: http://data.europa.eu/88u/dataset/S2156_88_1_468_ENG (accessed 21.04.2020). 2 Ibid. 3 Ibid.…”
Section: Studies Of Environmental Risk Perception In Baltic Region Statesmentioning
confidence: 99%
“…The main variable analyzed is the willingness of people to share their personal information securely to improve energy efficiency. Different variables are used to develop and frame the analysis, the selected items for the model are similar to those routinely used in environmental studies with the Eurobarometer datasets [10,43,44,[53][54][55][56][57][58][59][60][61][62][63]. As a novel aspect and contribution of the present study is that the latest Eurobarometer dataset item on willingness to share personal information for energy efficiency has yet to be operationalized at the time of this writing, particularly the question: "Public services could be improved if people shared some of their personal information.…”
Section: Variablesmentioning
confidence: 99%